2011
DOI: 10.1039/c0jm02171g
|View full text |Cite
|
Sign up to set email alerts
|

Probing magnetic interactions in columnar phases of a paramagnetic gold dithiolene complex

Abstract: A novel radical gold dithiolene complex exhibits a hexagonal columnar mesophase, as confirmed by optical microscopy, DSC analysis and X-ray diffraction. The extent of delocalization of the spin density in such a complex was analyzed by EPR. Temperature dependent magnetization measurements reveal that the global magnetic moment is remarkably affected at the liquid-crystalline phase transition with a marked hysteresis signature, rare behavior among the few described paramagnetic discotic phases. In addition, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 59 publications
3
39
0
Order By: Relevance
“…Several research groups originally studied the mesomorphous properties for the neutral nickel-dithiolene complexes (42)(43)(44)(45)(46). Fourmigué and co-workers reported multifunctional neutral golddithiolene complexes, which showed the magnetic mesophase with strongly near infrared (NIR) absorption band around 1.5 µm (47), or a hexagonal columnar mesophase with a high sensitivity of magnetic interactions to external stimuli (48). Recently, we designed and synthesized a novel nickel-dithiolene ion-pair salt, [C 6 -Apy][Ni(mnt) 2 ] (where C 6 -Apy + = 4-amino-1hexylpyridinium).…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups originally studied the mesomorphous properties for the neutral nickel-dithiolene complexes (42)(43)(44)(45)(46). Fourmigué and co-workers reported multifunctional neutral golddithiolene complexes, which showed the magnetic mesophase with strongly near infrared (NIR) absorption band around 1.5 µm (47), or a hexagonal columnar mesophase with a high sensitivity of magnetic interactions to external stimuli (48). Recently, we designed and synthesized a novel nickel-dithiolene ion-pair salt, [C 6 -Apy][Ni(mnt) 2 ] (where C 6 -Apy + = 4-amino-1hexylpyridinium).…”
Section: Introductionmentioning
confidence: 99%
“…Evolution of global magnetic moment as a function of temperature during heating and cooling cycles around the crystal/mesophase transition at a rate of 10 K min –1 (insert: DSC curves of compound [Au(dphedt) 2 ] 0 with n = 12 around the crystal/mesophase transition (2 nd heating curve (top) and 1 st cooling curve (bottom)). Reproduced from ref . Copyright (2011), with permission from The Royal Society of Chemistry.…”
Section: Liquid Crystalsmentioning
confidence: 99%
“…Despite the absence of hydrogen‐bond donor fragments, the gelation properties of the paramagnetic (S = 1/2) neutral gold complex [Au(dphedt) 2 ] 0 with n = 12 have been evaluated . This compound was found to be able to form brittle gels in linear alkanes (C6–C12) (Figure a).…”
Section: Gelsmentioning
confidence: 99%
“…The mesomorphous neutral nickel-dithiolene complexes, with focus on the aspect of mesophase with crystalline to liquid crystal transition behaviors, have been studied by . Most recently, Fourmigué et al have reported multifunctional neutral gold-dithiolene complexes, which show the magnetic mesophases with strongly near infrared (NIR) absorption band around 1.5 μm [21], or a hexagonal columnar mesophase with a high sensitivity of magnetic interactions to external stimuli [22]. For the neutral and mesogenic metal-dithiolene complexes, both mesophase and other functional properties arise from the metal-dithiolene unit, indicating that the tailoring of mesophase and other functional properties could be realized by singly alteration of the dithiolene ligands or metal ions.…”
mentioning
confidence: 99%